An Exploratory Study of Motivation for the Young Adult Consumers To Purchase Luxury Brands - Shumsher JB Rana, Sarthak (2012)
The market for luxury brands is increasing at an enormous rate as there is constant increase in the demand for such goods. This dissertation aims at identifying motivations among the young adult consumers (between the age group of 21-27) to purchase luxury brands. The existing literature on luxury is reviewed along with some of the motivational theories. The author uses the framework developed by Tynan, McKechnie and Chhoun (2009) to understand various values derived from the purchase of luxury brands and uses them to analyze the findings of the study. The current study is carried out to understand what consumers think of luxury, why they buy luxury and what motivates them to buy luxury brands. The author seeks to find answers to these questions by conducting qualitative interview. For this purpose 5 participants from UK and 5 participants from India are selected to compare the motivations for luxury brand purchase between the participants from the two countries. The author identifies that utilitarian value and symbolic or expressive value derived from the consumption of luxury brands are the main driving forces to consume luxury brands. Finally the author discusses the managerial implications and provides suggestions for future research in the conclusion.